IMPACT OF FOOD SUPPLEMENTATION WITH RADIX ISATIDIS POLYSACCHARIDE ON QUALITY OF EGG, FUNCTION OF IMMUNE AND INTESTINAL HEALTH IN LAYING HENS - MANZOOR, H; KHAN, M; FARAZ, A; IRFAN, M; RIZWAN, M; ALAM, N; RAUF, U; ZEB, K; SOHAIL, M (Biological and Clinical Sciences Research Journal, 2024)
The introduction of dietary supplementation with Radix Isatidis polysaccharide explores the potential effects on poultry health, focusing on egg quality, immune function, and intestinal health in hens. The study’s main objective is to find the effects of dietary supplementation with radix isatidis polysaccharide on egg quality, immune function, and intestinal health in hens. The study employed a randomized controlled trial design to investigate the effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens. 125 laying hens were included in the study and randomly assigned to experimental and control groups. The experimental group received a diet enriched with Radix Isatidis polysaccharide, while the control group received a standard diet without the supplementation. The study assessed egg quality parameters, revealing that the experimental group exhibited superior egg characteristics compared to the control group. The eggs from the experimental group had a higher weight (65g) and thicker shells (0.4mm) compared to the control group with egg weight of 60g and shell thickness of 0.35mm. Additionally, the yolk color was more vibrant in the experimental group (Yolk Color: 8) compared to the control group (Yolk Color: 6), and the albumen height was greater in the experimental group (Albumen Height: 10mm) than in the control group (Albumen Height: 9mm). It is concluded that Radix Isatidis Herbal Residue (RIHR), derived from the remnants of R. isatidis extraction, holds significant promise as a dietary supplement in laying hen production.